Humerus Post Orif Hari Ke 0 Di Rsop Dr. R. SoeharsoSurakarta - , Viola Satriana; , Enita Dewi, S.Kep., Ns (2016)
Surgery or operation is the action that uses invasive way by making an incision and ends with closure and suturing. As a result of the surgical procedure, the patient will experience a sense of discomfort or pain disorders. Pain is a sensation that is very unpleasant, varies among individuals and can affect a person's entire mind. One nonpharmacological measures to reduce or control the pain with deep breathing does relax. The purpose of writing a scientific paper is to determine the general idea of nursing care with a fracture of the left humerus and reporting nonpharmacological measures to the reduction of pain in patients. The method used descriptive case studies and using the nursing process approach. The nursing process starts from the assessment and evaluation. After 3x24-hour nursing care for patients post surgery fracture of the humerus with acute pain issues resolved partially and continued intervention. The influence nonpharmacological therapy in reducing pain scale. Acute pain problems solved most of that needs further treatment, the role of families is indispensable for the success of nursing care.